Therapeutic Management of Snake Bite in a Surti Buffalo - Sadhu, Dasharath B.; Dave, Keshank M.; Patel, Rajkumar K.; Raval, Sunant K.; Sarviya, Nitesh P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Snake bite is an acute life-threatening and hazardous timelimiting medical emergency common in animals such as cattle, sheep, goats and dogs in areas with heavy rainfall and humid climate. There are nearly 216 species of snakes in India, of which 60 are considered poisonous (Gupta and Peshin, 2014).